1996
DOI: 10.1111/j.1432-1033.1996.00056.x
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine Increases Argininosuccinate Synthetase mRNA Levels in Rat'Hepatocytes

Abstract: Glutamine, one of the most efficient substrates in the urea cycle, was found to induce the accumulation of argininosuccinate synthetase (ASS) mRNA in primary cultured rat hepatocytes. The inducing action of glutamine was obtained at various stages of development and a half-maximal effect was observed at about 3 mM glutamine. This effect was apparent from 6 h and persisted for at least 48 h. NH,C1 addition up to 5 mM did not significantly change the ASS mRNA level. Like glutamine, hypoosmotic medium and aminois… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
25
1

Year Published

1996
1996
2008
2008

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 26 publications
1
25
1
Order By: Relevance
“…3 specifies that this effect of glutamine on the [3-actin mRNA level was dose-dependent and its half-maximum stimulatory effect was obtained at about 3 mM. Interestingly, this value was reported for the half-maximum effect of glutamine on the argininosuccinate synthetase mRNA level in cultured rat hepatocytes; in these experiments, the glutamine-induced cell swelling had been reported to be responsible for this effect [2].…”
Section: Glutamine Increased the ~-Actin Mrna Level Through Amentioning
confidence: 69%
See 1 more Smart Citation
“…3 specifies that this effect of glutamine on the [3-actin mRNA level was dose-dependent and its half-maximum stimulatory effect was obtained at about 3 mM. Interestingly, this value was reported for the half-maximum effect of glutamine on the argininosuccinate synthetase mRNA level in cultured rat hepatocytes; in these experiments, the glutamine-induced cell swelling had been reported to be responsible for this effect [2].…”
Section: Glutamine Increased the ~-Actin Mrna Level Through Amentioning
confidence: 69%
“…Thus, hypoosmolarity has been reported to increase the actin mRNA level in isolated rat hepatocytes [1], the argininosuccinate synthetase mRNA level in cultured rat hepatocytes [2] and the c-jun mRNA level in rat hepatoma cells [3]. Conversely, hypoosmolarity has been reported to decrease the phosphoenolpyruvate carboxykinase [4,5] and the tyrosine aminotransferase mRNA levels [5] in both perfused rat liver and H4IIE rat hepatoma cells.…”
Section: Introductionmentioning
confidence: 99%
“…This amino acid, via glutaminase, provides the first ''N'' atom for urea synthesis. Quillard et al (1996Quillard et al ( , 1997 showed that glutamine increases argininosuccinate synthase (ASS) activity and expression in cultured hepatocytes from fetal and adult rats. ASS converts citrulline to arginosuccinate.…”
Section: Cell Metabolismmentioning
confidence: 99%
“…), the key enzyme of arginine synthesis, we observed that the mechanism involved might depend on the cell type studied. Indeed, we previously reported that the glutamine-induced cell swelling was involved in hepatocytes because hypo-osmolarity totally mimicked the glutamine stimulating effect on the mRNA level (10); but this was not the case in Caco-2 cells, a human intestinal cell line (17). The present work was therefore begun to specify the molecular mechanism involved in the stimulating effect of glutamine on ASS gene expression in Caco-2 cells.…”
mentioning
confidence: 99%
“…Among amino acids, glutamine, which is the most abundant circulating amino acid, stimulates or inhibits the expression of various genes. This includes (i) intracellular proteins such as transcription factors (3,4), constitutive proteins of the cytoskeleton (5,6) and of the extracellular matrix (7), heat shock proteins (8) or metabolic enzymes (9,10); (ii) membrane proteins such as the transport system (11); and (iii) secreted proteins such as acute phase proteins (12), cytokines (13,14), and growth factor (15). However, the molecular mechanism(s) involved in the glutamine effect is not totally understood and may depend on the cell type studied.…”
mentioning
confidence: 99%